Imidazolinone resistance, yield potential and agronomic performance of the irrigated rice cultivar BRS A706 CL - Rangel,Paulo Hideo Nakano (2022)
Abstract Cultivar BRS A706 CL is a new rice cultivar, resistant to herbicides of the chemical group of imidazolinones, with a yield potential of 15,635 kg ha-1. It has intermediate maturation, lodging tolerance, the stay green trait, moderate rice blast resistance, a high milling yield and premium grain quality.